Kekuasaan Dan Wewenang Dalam Perspektif Sistem Pemerintahan - Shabrina Rizkiyani; Saeful Mujab (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This article reviews the differences and relationships between political power and authority from a government system perspective. Political power includes the ability to influence the behavior of others, while political authority relates to the rights or authority granted by law or the constitution. The method used is data collection (library study) with the aim of collecting conceptual information and data from various sources such as journals, books, previous research, as well as various previously published scientific articles. This article reveals how political power and authority have an important interconnected relationship in political decision making. The results provide a deeper understanding of how these two concepts influence the dynamics of government systems.